Mutations in CSTA, encoding cystatin A, underlie exfoliative ichthyosis and reveal a role for this protease inhibitor in cell-cell adhesion - Blaydon, Diana C.; Nitoiu, Daniela; Eckl, Katja-Martina; Cabral, Rita M.; Bland, Philip; Haußer-Siller, Ingrid; van Heel, David A.; Rajpopat, Shefali; Fischer, Judith; Oji, Vinzenz; Zvulunov, Alex; Traupe, Heiko; et al. (The American journal of human genetics, 2011)
Autosomal-recessive exfoliative ichthyosis presents shortly after birth as dry, scaly skin over most of the body with coarse peeling of nonerythematous skin on the palms and soles, which is exacerbated by excessive moisture and minor trauma. Using whole-genome homozygosity mapping, candidate-gene analysis and deep sequencing, we have identified loss-of-function mutations in the gene for protease inhibitor cystatin A (CSTA) as the underlying genetic cause of exfoliative ichthyosis. We found two homozygous mutations, a splice-site and a nonsense mutation, in two consanguineous families of Bedouin and Turkish origin. Electron microscopy of skin biopsies from affected individuals revealed that the level of detachment occurs in the basal and lower suprabasal layers. In addition, in vitro modeling suggests that in the absence of cystatin A protein, there is a cell-cell adhesion defect in human keratinocytes that is particularly prominent when cells are subject to mechanical stress. We show here evidence of a key role for a protease inhibitor in epidermal adhesion within the lower layers of the human epidermis.